Managing Yellow and Purple Nutsedge in Florida Strawberry Fields - Andrew W. MacRae (EDIS)
HS1175, a 3-page illustrated fact sheet by Andrew W. MacRae, gives management guidelines for these perennial weeds that are well adapted for growth in plasticulture production systems. Published by the UF Department of Horticultural Sciences, May 2010.